1982
DOI: 10.1515/znc-1982-3-411
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan and Protein, the Major Cell Wall Constituents of the Obligate Halophilic Bacterium Rhodospirillum salexigens

Abstract: The obligate halophilic member of Rhodospirillaceae, Rhodospirillum salexigens, does not contain lipopolysaccharide in its thin and delicate gram-negative type cell wall. Major constituents are protein (approximately 70% of dry weight) and peptidoglycan (murein).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This phototrophic bacterium grows at sodium chloride concentrations between 5 and 20%. The cells react negatively on Gram staining, their cell walls contain peptidoglycan in surprisingly small amounts, and proteins seem to be firmly associated with this peptidoglycan (25). Electron microscopic studies showed an outermost layer outside a very thin so-called "outer membrane" bilayer (7).…”
mentioning
confidence: 99%
“…This phototrophic bacterium grows at sodium chloride concentrations between 5 and 20%. The cells react negatively on Gram staining, their cell walls contain peptidoglycan in surprisingly small amounts, and proteins seem to be firmly associated with this peptidoglycan (25). Electron microscopic studies showed an outermost layer outside a very thin so-called "outer membrane" bilayer (7).…”
mentioning
confidence: 99%